The Mechanism, Calculation and Simulation of Power Loss for IGBT Modules - WANG Yangang; DAI Xiaoping; WU Yibo; JONES Steve; LIU Guoyou (Kongzhi Yu Xinxi Jishu)
In this paper, the mechanism of IGBT power loss was analyzed, the definition and calculation of the power loss were discussed based on the characteristics of conduction and switching. The power loss of IGBT and FWD can be estimated by using the IGBT module datasheet, and be simulated by PSIM. Finally, the power loss and maximum junction temperature of IGBT module in an inverter circuit were calculated by equations and PSIM.